Daya Saing, Liberalisasi, Dan Industrialisasi Perdagangan Internasional : Analisis Konseptual - Jamila (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Competitiveness, liberalization and industrialization have a significant impact on the growth of international trade. This journal aims to determine the competitiveness, liberalization and industrialization of international trade. This research uses library research, which places more emphasis on reviewing books in libraries directly or from digital libraries, journals, reports and other references that can be used as references in this research. The results of this research show that the level of competitiveness of a country will greatly impact the growth of international trade. Countries that have strong competitiveness tend to have better trade performance and are able to attract foreign investment. Countries that implement progressive liberalization policies tend to experience increases in exports and imports.